Implementasi Pencegahan Pencemaran Lingkungan Laut Oleh Zat Berbahaya Menurut Marpol Annex II diatas Kapal (Studi Kasus : MV. Tanto Handal) - Ramadhan, Muhammad Rifaldo; Basuki, Minto (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2025)
Seawater pollution due to dangerous chemicals such as dangerous toxic liquids spilled from ship operational activities often occurs. Hazardous chemical spills are a type of pollution that has quite a large impact in the long term. The activity of disposing of ballast water is also a form of marine environmental pollution which, when referring to UNCLOS, includes marine pollution originating from ships. The ballast water system is a system whose presence is mandatory on a ship. This system uses sea water as ballast to keep the ship in balance when the ship is not carrying a load that matches its maximum capacity. Based on the problems above, the objectives to be achieved in this research are to analyze the implementation of MARPOL ANNEX II to prevent marine pollution and to analyze how to implement MARPOL ANNEX II to prevent and overcome marine pollution while on board an MV. TANTO HANDAL. This research was carried out while on board the ship to obtain data using qualitative research methods, so the author will use techniques by making direct observations on the objects being investigated and interviews with the ship's crew. The results of this research are the lack of ability of ship officers in explaining and giving direction on how to prevent marine pollution by dangerous substances to ship crews on board MV. TANTO HANDAL, such as the lack of firmness of the captains in providing direction and monitoring the daily work of the ship's crew, such as the disposal of used ship washing water and ballast water.